2018
DOI: 10.1002/jcb.27396
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin attenuates liver injury and inflammation in a cecal ligation and puncture induced sepsis mouse model

Abstract: Sepsis is a syndrome of life-threatening multiorgan dysfunction caused by host response dysregulation to infection. Ulinastatin (UTI), a serine protease inhibitor, possesses anti-inflammatory properties and has been suggested to modulate lipopolysaccharide-induced sepsis. However, little is known about the mechanism underlying its effects on sepsis. In the current study, we investigated the protective effect of UTI on liver injury in a cecal ligation and puncture (CLP)-induced sepsis of C57BL/6 mouse model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Even though we did not detect the changes of inflammatory mediators in the abdominal cavity, we here observed that acetic acid-induced infiltration of inflammatory cells in the peritoneum tissue decreased significantly after systemic administration of ulinastatin in H&E staining assay, which reinforced previous study that ulinastatin ameliorated the number of infiltrated inflammatory cell in cecal ligation and puncture induced sepsis. 59 In addition to the local inflammation evoked by acetic acid, the role of spinal inflammatory reaction, including glial activation and pro-inflammatory cytokines release, in acetic acidinduced writhing response has also been reported. [60][61][62] Previous studies verified that both minocycline and fluorocitrate were able to markedly reduce acetic acid-induced acute visceral nociception.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we did not detect the changes of inflammatory mediators in the abdominal cavity, we here observed that acetic acid-induced infiltration of inflammatory cells in the peritoneum tissue decreased significantly after systemic administration of ulinastatin in H&E staining assay, which reinforced previous study that ulinastatin ameliorated the number of infiltrated inflammatory cell in cecal ligation and puncture induced sepsis. 59 In addition to the local inflammation evoked by acetic acid, the role of spinal inflammatory reaction, including glial activation and pro-inflammatory cytokines release, in acetic acidinduced writhing response has also been reported. [60][61][62] Previous studies verified that both minocycline and fluorocitrate were able to markedly reduce acetic acid-induced acute visceral nociception.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no studies on the concentration of HNE adducts in sepsis patients in the literature. However, studies using animal models of sepsis showed an increased HNE concentration in blood or overexpression in organ tissues after sepsis initiation [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming of inflammation signaling is an important therapeutic target. In recent studies, ulinastatin has been demonstrated to attenuate I/R injury (including cerebral ischemia) in multiple stressed organs by suppressing inflammation (23,26,27). ICAM-1 is a chemokine that recruits immune cells to evoke an inflammatory response; IL-6, IL-1β, and IL-18 were important inflammatory cytokines secreted under nucleotide oligomerization domain (NOD)-like receptor 3 (NLRP3)enabled inflammation (28).…”
Section: Discussionmentioning
confidence: 99%